Intermittent food restriction: repercussions in the regulation of hypothalamic energy homeostasis and adipose tissue - Rosas Fernández, Mariana (2018)
The practice of intermittent food restriction (IFR) along its variations, is used by individuals with an intentional loss of body mass. There is scientific evidence favorable to this practice; however, studies showing the longterm consequences and their impact on the control of energy homeostasis at the level of the central nervous system (CNS) are insufficient. Considering the increase in its use, as well as in its recommendation and the great controversy existing in the bibliography, the present review aims to show the effects of RAI on the central regulation of energy homeostasis reported in the literature.